Arabic Stylistic Ibn Al-Khatib Al-Ghernati's Procedures Of Discourse In Prohibitions And Sermons/ الأسلوبية العربية إجراءات الخطاب عند ابن الخطيب الغرناطي في المحرمات والخطب - Omar, Ahmad (Ijaz Arabi Journal of Arabic Learning, 2025)
Ibn al-Khatib's artistic prose is characterized by a variety of stylistic procedures in the discourse, as he diversified the modes of reception between authority, peers, and the governed, and he benefited in his discourse procedures from his vast culture, as Ibn al-Khatib brought together the culture of Andalusia. The reasons for the prose andity of his rhetorical procedures, as they mediate between direct stylistics and suggestive patterns, through comprehensive procedures, which consume all his prose, and share stylistic pillars that are not devoid of any genius statement, distributed among various styles in different books totaling over sixty publications. The research investigated his methods cautiously and traced the stylistics of discourse according to this collective space of his rhetorical procedures, especially since they are consistent in their general threads. However, I have found, after reading his non-lost product, a comprehensive reading, that there is a special style, characterized by each prose trend, while maintaining the major standard procedures that make the prose attributable to him, so I turned to one of his types, that related to prohibitions and sermons, with a rooting of the standard procedures that are common in his prose.